The archived web: doing history in the digital age - Brügger, Niels 1959- (Cambridge, Massachusetts: The MIT Press, 2018)
"How will the history of the present be written? As life continues to move online, the web becomes ever more important for an understanding of the past. This book offers an original theoretical framework for approaching the web of the past, both as a source and as an object of study in its own right"--
Doing web history in the digital age -- The digital and the web -- Five analytical web strata -- Cases of web history -- Archiving the web -- The web of the past : where to find what? -- The web of the past as a historical source -- Scholarly use of the archived web -- Towards a source criticism of the archived web -- On the edge of the web -- Conclusion : the future of web history.
Keywords: World Wide Web